Kitāb shināsi-yi āthār-i Fārsi-yi chāp shuda dar shibh-i qāra (Hind, Pākistān, Banglādish), 1160-1387/1195-1428/1781-2007. Volume 1 - Nūshāhī, ʿĀrif (Miras Maktoob, ISBN: 9789004365452., 2019)
Gutenberg's invention of the printing press in the fifteenth century marked the beginning of a new era in the transmission of knowledge, the spread of ideologies, and the administration of peoples. Even if the Mughal emperor Jahāngīr (d. 1627), when presented with a printed copy of the Gospels, expressed his interest in exploring the possibilities for the printing of texts in nastaʿlīq in movable type, it would take another two hunderd years before the people of the Indian subcontinent started printing themselves. In the 1820's, when Indians began using western printing techniques to reproduce texts in local languages, they preferred lithographs over movable type. The former required less technology, were typographically superior, and also closer to the traditional reading experience. Movable type came only later. The printing of Persian texts had its heyday between the 1820's and 1850's. The present inventory shows the immense richness of two centuries of Persian printing on the Indian subcontinent. 4 vols; volume 1.